Chemical weapons convention act, 2000 (New Delhi, 2011)
A Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on their Destruction was signed on behalf of the Government of India at Paris on 14th January, 1993. India having ratified the said Convention, had to make provisions for giving effect thereto. Accordingly the Chemical Weapons Convention Bill was introduced in the Parliament.
Keywords: "Chemicals weapons convention act, 2000"